DHX9-mediated epigenetic silencing of BECN1 contributes to impaired autophagy and tumor progression in breast cancer via recruitment of HDAC5 - Ziyang Li; Fang Liu; Fengbei Li; Guopeng Zeng; Xin Wen; Jianan Ding; Jueyu Zhou (Cell Death and Disease)
Abstract Autophagy is closely linked to tumorigenesis, progression and metastasis. DHX9 is a member of the DExD/H-box helicase family and plays important roles in transcription, translation, RNA editing and non-coding RNA synthesis. Mounting evidence demonstrates that aberrant expression of DHX9 is associated with the development and progression of several tumors. However, whether DHX9 regulates autophagy deficiency in breast cancer (BC) remains unknown. Herein, we found that DHX9 expression was frequently elevated in BC cells and tissues, which suggested poor survival. The viability and motility of BC cells were irritated by enhanced DHX9 expression. Meanwhile, reduced DHX9 expression postponed tumor development both in vitro and in vivo. Subsequent research revealed that DHX9 knockdown suppressed the activation of the mTOR signaling pathway and accelerated autophagic flux by promoting the formation of autophagosomes in BC cells. Mechanistically, DHX9 occupied the proximal promoter of BECN1 and repressed its transcription. DHX9-mediated BECN1 inhibition required histone deacetylase (HDAC) activity. HDAC5 was recruited to the nucleus and co-localized with DHX9 at the BECN1 promoter, mediating the deacetylation of histone H3 and ultimately inhibited BECN1 transcription. Importantly, the tumor-suppressive effect of DHX9 knockdown was reversed by BECN1 downregulation. In conclusion, the previously unrecognized significance of DHX9 in mediating the epigenetic silencing of BECN1, which is essential for autophagy and tumorigenesis, highlights its potential as an effective biomarker as well as a prospective therapeutic candidate for BC.